Analysis Of Salary Of Permanent Employees And Contract Employees On The Medicom Campus Using The K – Means Algorithm - Harahap, Leliana; Purba, Sartika Dewi; Situmorang, Sutrisno; Panggabean, Jonas Franky R; Sirait, Kamson (Journal of Intelligent Decision Support System (IDSS), 2023)
The Medicom campus is a place of work that provides jobs to the community. In work, employee status cannot be separated, namely permanent employees and contract employees. In employee status, employee salaries can be determined. In determining employee salaries, there are several problems that can disrupt employee performance at work. For this reason, a method is needed to determine employee salaries. One method that can be used is the K-Means Clustering Algorithm. Which is considered quite effective in determining the suitability of salaries for permanent employees and contract employees. By creating clusters to make it easier for finance workers to record and determine and adjust employee salaries based on their status.